Anti‐Counterfeiting White Light Printed Image Multiplexing by Fast Nanosecond Laser Processing. Issue 2 (16th November 2021) - Dalloz, Nicolas; Le, Van Doan; Hebert, Mathieu; Eles, Balint; Flores Figueroa, Manuel A.; Hubert, Christophe; Ma, Hongfeng; Sharma, Nipun; Vocanson, Francis; Ayala, Stéphane; Destouches, Nathalie
Abstract: Passive plasmonic metasurfaces enable image multiplexing by displaying different images when altering the conditions of observation. Under white light, three‐image multiplexing with polarization‐selective switching has been recently demonstrated using femtosecond‐laser‐processed random plasmonic metasurfaces. Here, the implementation of image multiplexing is extended, thanks to a color‐search algorithm, to various observation modes compatible with naked‐eye observation under incoherent white light and to four‐image multiplexing under polarized light. The laser‐processed random plasmonic metasurfaces enabling image multiplexing exhibit self‐organized patterns that can diffract light or induce dichroism through hybridization between the localized surface plasmon resonance of metallic nanoparticles and a lattice resonance. Improved spatial resolution makes the image quality compatible with commercial use in secured documents as well as the processing time and cost thanks to the use of a nanosecond laser. This high‐speed and flexible laser process, based on energy‐efficient nanoparticle reshaping and self‐organization, produces centimeter‐scale customized tamper‐proof images at low cost, which can serve as overt security features. Abstract : Up to four images are encoded in a single random plasmonic metasurface created by fast nanosecond laser processing. Each laser‐induced pixel exhibits various colors in different observation modes, which can be controlled independently to enable multiplexing. The approach, different from holography, makes possible the observation of various images on the same support by the naked eye under different observation angles.